Headache in an emergency room in Brazil - Bigal, Marcelo; Bordini, Carlos Alberto; Speciali, José Geraldo (São Paulo Medical Journal, 2000)
CONTEXT: When experiencing a headache attack, Brazilian patients usually look for a primary care service, where they are seen by general clinicians. In the town of Ribeirão Preto, these clinicians routinely refer patients to the Emergency Room of the University Hospital. OBJECTIVE: The objective of this study was to evaluate the quality of primary care by analyzing retrospectively the medical records of patients with a complaint of headache seen in this emergency room during the year of 1996. DESIGN: retrospective study. SETTIING: Emergency Room of the Universital Hospital, Ribeirão Preto, São Paulo, reference unit. PARTICIPANTS:1254 patients. The patients who sought the Emergency Room (ER) of the University Hospital of Ribeirão Preto, during the year of 1996 with a complaint of headache were studied retrospectively. MAIN MEASUREMENTS: Etiology, age, diagnosis, secondary cause, laboratory tests. RESULTS: Of the 1254 patients seen (61% women), 1190 (94.9%) were discharged after the administration of parenteral analgesics before they had spent 12 hours in the room. Only 64 (5.1%) patients remained for more than 12 hours. Of the patients who spent less than 12 hours in the room, 71.5% had migraine or tension type headache and did not require subsidiary exams for diagnosis. Of the patients who spent more than 12 hours in the room, 70.3% had secondary headaches. CONCLUSIONS: We conclude the primary care for headache is unsatisfactory in the Ribeirão Preto region. Many patients with primary headache are referred to tertiary care services, indicating the need for the dissemination of the diagnostic criteria of the International Headache Society to general practitioners.